AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KRATOM (Mitragyna speciosa Korth.) TERHADAP BEBERAPA BAKTERI PENYEBAB JERAWAT - Maria Ulfah; Irma Erika Herawati; Endah Kartikawati (Jurnal Buana Farma, 2024)
Acne is a common disease on the surface of the skin of the face. It will appear when the oil glands are too active and is generally followed by a bacterial infection that will cause inflammation. Bacteria that can cause acne include Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. The plant that has antibacterial activity is kratom (Mitragyna speciosa Korth). Kratom leaves have secondary metabolites that can act as antibacteria, such as alkaloids, flavonoids, and saponins. The study aims to determine the antibacterial activity of ethanol extract against some bacteria causing acne using disc diffusion methods. The concentrations of the test sample ethanol extract of kratom leaves used were 60%, 30%, 15%, and 12.5%, with the positive controls used being chloramphenicol. The results of the study showed that ethanol extract at all concentrations had a barrier zone against the growth of the bacteria P. acnes, S. aureus, and S. epidermidis with a moderate barrier response category. Where best activity is shown at a concentration of 60% kratom leaf ethanol extract against P.acnes and S.aureus